Loop-Mediated Isothermal Amplification for Influenza A (H5N1) Virus - Shanthi Jayawardena; Chung Y. Cheung; Ian Barr; Kwok H. Chan; Honglin Chen; Yi Guan; J.S. Malik Peiris; Leo L.M. Poon (Emerging Infectious Diseases, 2007)
We describe a 1-step reverse-transcription loop-mediated isothermal amplification assay for detection of highly pathogenic avian influenza A (H5N1) viruses. The assay was tested by using a panel of highly pathogenic H5N1 subtypes isolated over the past 10 years and clinical specimens. The assay produced negative results for all non-H5N1 subtypes.